Evidence-Based Smart Transition Strategies for Long-Distance Commuters in Beijing - Zhao, Xu; Zhang, Zhehao; Guo, Wenbo; Zhou, Yufang; Papaix, Claire; Sun, Qingfeng (Frontiers in Future Transportation, 2022)
Building a sustainable and eco-friendly transport system is crucial to tackling global challenges such as climate change, as transport can be seen as one of the main sources of air pollution and CO2 emissions in megacities, particularly in developing countries. By bringing together multiple modes of travel, and combining different transport provider options into a single service, Mobility-as-a-Service (MaaS) could offer an effective way to help build a sustainable city by improving public transport services. However, the strategies used to develop MaaS, vary in different cities based on their specific multimodal transport facilities and service. Many residents of Beijing have to contend with long-distance commuting, which may adversely affect individuals’ travel experience and satisfaction and is, therefore, a key issue for transport development in Beijing. Using Beijing as a case study, we carried out in-depth interviews and thereby captured long-distance commuters’ concerns and needs concerning their commuting experiences. Our findings show that long-distance commuters are primarily concerned about the following multimodal commuting scenarios: “Underground+bicycle”, “Underground+taxi”, “Underground+private car”, and “Underground+bus”. Therefore, we suggest that the priority should be to develop a MaaS model for Beijing that focuses on the integration of multimodal transport connected to the underground rail system.